Decreased Ficolin-3-mediated Complement Lectin Pathway Activation and Alternative Pathway Amplification During Bacterial Infections in Patients With Type 2 Diabetes Mellitus - Barkai, László József; Sipter, Emese; Csuka, Dorottya; Prohászka, Zoltán; Pilely, Katrine; Garred, Peter; Hosszúfalusi, Nóra (Frontiers in Immunology, 2019)
Bacterial infections are frequent and severe in patients with diabetes mellitus. Whether diabetes per se induces functional alterations in the complement system hampering activation during infection is unknown. We investigated key elements of the complement system during bacterial infections in patients with type 2 diabetes mellitus (T2DM) and compared them to non-diabetic (ND) individuals. Using a prospective design, we included 197 T2DM and 196 ND subjects, all with clinical diagnosis of acute community-acquired bacterial infections. Functional activities of the ficolin-3-mediated lectin (F3-LP), mannose binding lectin-mediated lectin- (MBL-LP), classical (CP) and alternative pathways (AP), as well as concentrations of complement activation products C4d and sC5b-9 were determined. Functional in vitro activities of F3-LP and AP were significantly higher in T2DM than in ND subjects, (median 64% vs. 45%, p=0.0354 and 75 vs. 28%, p=0.0013, respectively), indicating a decreased in vivo activation and lack of consumption of F3-LP and AP in T2DM patients, whereas no difference in functional capacities of CP and MBL-LP were observed between T2DM and ND subjects. Diminished F3-LP and AP activation was most pronounced in diabetic patients with urinary tract infections with positive microbiological culture results for Escherichia coli bacteria. In the T2DM group 3-months mortality significantly associated with diminished F3-LP and AP, but not with CP activation. Concentrations of C4d and sC5b-9 were significantly lower in the T2DM than in ND patients. In conclusion, we found impaired F3-LP activation and lack of AP amplification during bacterial infections in patients with type 2 diabetes, compared to non-diabetic subjects, suggesting a diminished complement mediated protection to bacterial infections in T2DM.